Feeding in the first six months of life is associated with the probability of having bronchiolitis: a cohort study in Spain - Inés Gómez-Acebo; Carolina Lechosa-Muñiz; María Paz-Zulueta; Trinidad Dierssen Sotos; Jéssica Alonso-Molero; Javier Llorca; María J. Cabero-Perez (BMC, 2021)
Abstract Background Breastfeeding is associated with lower incidence and severity of lower respiratory tract disease. However, little is known about the relationship between feeding type and breastfeeding duration with bronchiolitis in a child's first year. Methods A prospective cohort study of 969 newborn babies were followed-up for 12 months to determine breastfeeding duration, feeding type, feeding trajectory, and bronchiolitis episodes at Marqués de Valdecilla University Hospital, Spain in 2018. Type of feeding was recorded by interviewing mothers at the time of hospital discharge and at 2, 4, 6, 9 and 12 months of life, in three categories: breastfeeding, mixed feeding and infant formula. Type of feeding at hospital discharge refers to feeding from birth to discharge. In any other times studied, it refers to feeding in the last 24 h. The association between the feeding type and bronchiolitis was analysed using logistic regression. Poisson regression was used to evaluate the association between feeding type and the number of bronchiolitis episodes with Kaplan-Meier estimators presenting the cumulative probability of suffering bronchiolitis. The results were adjusted for mother and child characteristics. Results Our data shows exclusive breastfeeding and mixed breastfeeding reduce the number of episodes of bronchiolitis. Regarding feeding at 4 months, exclusive breastfeeding reduced by 41% the number of episodes of bronchiolitis (adjusted incidence Ratio (aIR) 0.59, 95% CI 0.46, 0.76) and mixed feeding by 37% (aIR 0.63, 95% CI 0.47, 0.86). Moreover, changing from exclusive breastfeeding to mixed feeding increased the incidence of bronchiolitis compared with continuing exclusive breastfeeding. An early swap to mixed breastfeeding before months 2 or 4, was associated with a reduced the number of episodes of bronchiolitis, (aIR 0.53, 95% CI 0.39, 0.73 if introduction of mixed breastfeeding before month 2, and aIR 0.61, 95% CI 0.45, 0.83 if introduction of mixed breastfeeding before month 4), when compared with infant formula alone. Conclusions Any breastfeeding was associated with lower incidence of bronchiolitis and number of episodes of bronchiolitis in the first year of life. Consequently, promoting programmes facilitating exclusive or mixed breastfeeding would be a relevant measure in the prevention of bronchiolitis.